Probing the interactions between ionic liquids and water: experimental and quantum chemical approach - Khan, Imran (2016)
For an adequate choice or design of ionic liquids, the knowledge of their interaction with other solutes and solvents is an essential feature for predicting the reactivity and selectivity of systems involving these compounds. In this work, the activity coefficient of water in several imidazolium-based ionic liquids with the common cation 1-butyl-3-methylimidazolium was measured at 298.2 K. To contribute to a deeper insight into the interaction between ionic liquids and water, COSMO-RS was used to predict the activity coefficient of water in the studied ionic liquids along with the excess enthalpies. The results showed good agreement between experimental and predicted activity coefficient of water in ionic liquids and that the interaction of water and ionic liquids was strongly influenced by the hydrogen bonding of the anion with water. Accordingly, the intensity of interaction of the anions with water can be ranked as the following: [CF3SO3](-) < [SCN](-) < [TFA](-) < Br(-) < [TOS](-) < Cl(-) < [CH3SO3](-) [DMP](-) < [Ac](-). In addition, fluorination and aromatization of anions are shown to reduce their interaction with water. The effect of temperature on the activity coefficient of water at infinite dilution was measured by inverse gas chromatography and predicted by COSMO-RS. Further analysis based on COSMO-RS provided information on the nature of hydrogen bonding between water and anion as well as the possibility of anion-water complex formation.